Do firms still need to be social? Firm generated content in social media. Issue 2 (10th August 2018) - Poulis, Athanasios; Rizomyliotis, Ioannis; Konstantoulaki, Kleopatra
Abstract : Purpose: The purpose of this paper is to investigate how firm-generated content (FGC) impacts consumer brand awareness, brand loyalty and electronic word of mouth (eWOM), and how this, in turn, influences consumer purchase intention. Design/methodology/approach: In order to test this conceptual framework, statistical analysis was carried out employing structural equation modelling. Findings: The findings indicate that FGC has a positive impact on brand awareness, brand loyalty, eWOM and purchase intention. Furthermore, the results reveal that a link exists between consumer eWOM behaviour and brand awareness and loyalty. This study also demonstrates that company communication through Facebook and Instagram has a positive effect on consumer purchase intention. Finally, it has been shown that, regarding eWOM and purchase intention, FGC posted on Instagram has a greater impact on its users than that posted on Facebook. Originality/value: Consumer purchase intention is increasingly impacted by the growing use of social media by companies and marketers. This changing environment has opened up new challenges. However, there is still much work to be done in understanding the full effects of FGC communication, and how this influences consumer brand perception and purchase intention.